Obesity in Pediatric-Onset Multiple Sclerosis: A French Cohort Study. Issue 5 (September 2021) - Milles, Pauline; De Filippo, Gianpaolo; Maurey, Hélène; Tully, Thomas; Deiva, Kumaran
Abstract : Objective: To study the link between a high body mass index (BMI) in childhood and the occurrence of pediatric-onset multiple sclerosis (POMS) and to compare, within the MS population, the clinical-radiologic-biological characteristics, according to BMI. Methods: A case-control study comparing BMI data of 60 patients with POMS (39 girls and 21 boys) at Bicêtre Hospital with that of 113 non-neurologic controls NNCs (68 girls and 45 boys) and 18, 614 healthy controls HCs (9, 271 girls and 9, 343 boys) was performed. Crude BMI (cBMI), residual BMI (rBMI = measured BMI − expected BMI for age), z -score (rBMI/SD), and adult equivalent categories (International Obesity Task Force ≥25 = overweight, ≥30 = obese) were assessed. Results: In boys, cBMI and rBMI were significantly higher in patients with POMS compared with NNCs (cBMI: +2.9; rBMI: +2.95, p < 0.01) and HCs (cBMI: +2.04, p < 0.01). In girls, cBMI or rBMI did not differ between POMS and NNCs patients (cBMI p = 0.4; rBMI p = 0.44) but with HCs (cBMI +0.99, p < 0.01). CSF inflammatory markers increased with BMI in prepubertal patients ( p < 0.01), whereas vitamin D level at diagnosis was lower in boys with higher BMI ( p = 0.016). Increased BMI was not associated with clinical and radiologic disease characteristics. Conclusions: Overweight and obesity are more frequently observed at diagnosis, particularly in boys with POMS compared with non-neurologic controls and French HCs. Moreover, BMI is related to initial inflammation in the CSF in prepubertal patients with POMS suggesting an interaction between excess body fat, sexual hormones, and POMS occurrence.